“Is it me being too conservative or them being too insensitive?” A reflective thought on politeness in students’ short message service (SMS) - Alfima Azmi Imananda; Sunoko Setyawan (Jurnal Linguistik Terapan, 2014)
With the spirit of qualitative study, the researchers investigated the use of politeness strategies reflected in the students’ SMS to their lecturer. The messages were analyzed in the aspects of the politeness strategies employed by the students and the possible rationales underlying them. The results signify that the students failed to perform sufficient politeness strategies. Thus it is important for lecturers to explicitly integrate politeness issue in the classroom.